2017
DOI: 10.1128/jb.00859-16
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cyclic Di-GMP and Exopolysaccharide in Type IV Pilus Dynamics

Abstract: For Pseudomonas aeruginosa, levels of cyclic di-GMP (c-di-GMP) govern the transition from the planktonic state to biofilm formation. Type IV pili (T4P) are crucial determinants of biofilm structure and dynamics, but it is unknown how levels of c-di-GMP affect pilus dynamics. Here, we scrutinized how c-di-GMP affects molecular motor properties and adhesive behavior of T4P. By means of retraction, T4P generated forces of ϳ30 pN. Deletion mutants in the proteins with known roles in biofilm formation, swarming mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 54 publications
(86 reference statements)
2
36
0
Order By: Relevance
“…However, it is likely that one of the pilT paralogues powers retraction for this specific strain. On the other hand, T4P retraction powered by the retraction ATPase shows a wide range of forces, from 8 pN up to 150 pN (2,5,20,41). Taken together, we conclude that the retraction ATPase PilT consistently increases the force generated by T4P retraction in different bacterial species.…”
Section: Discussionmentioning
confidence: 60%
“…However, it is likely that one of the pilT paralogues powers retraction for this specific strain. On the other hand, T4P retraction powered by the retraction ATPase shows a wide range of forces, from 8 pN up to 150 pN (2,5,20,41). Taken together, we conclude that the retraction ATPase PilT consistently increases the force generated by T4P retraction in different bacterial species.…”
Section: Discussionmentioning
confidence: 60%
“…In P. aeruginosa , surface exploration is mainly accomplished by twitching motility, mediated by type IV pili, and does not appear to be influenced by levels of intracellular c-di-GMP when analyzing single cells ( 24 ). Interestingly, we found that correlations between c-di-GMP and motility during the lifetime of individual cells are weak.…”
Section: Resultsmentioning
confidence: 99%
“…Elongation and retraction are driven by dedicated ATPases (11,12). During the process of retraction, the T4P is capable of generating a very high force (13,14). Interestingly, the fact that the T4P elongate and retract dynamically affects the shape, dynamics, and sorting behavior of bacterial colonies (7,15,16).…”
Section: Introductionmentioning
confidence: 99%